2017
DOI: 10.1021/acs.jafc.6b05711
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Peptides Isolated from Casein Phosphopeptides Enhance Calcium and Magnesium Uptake in Caco-2 Cell Monolayers

Abstract: The ability of casein phosphopeptides (CPPs) to bind and transport minerals has been previously studied. However, the single bioactive peptides responsible for the effects of CPPs have not been identified. This study was to purify calcium-binding peptides from CPPs and to determine their effects on calcium and magnesium uptake by Caco-2 cell monolayers. Five monomer peptides designated P1 to P5 were isolated and the amino acid sequences were determined using LC-MS/MS. Compared with the CPP-free control, all fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 46 publications
(106 reference statements)
1
25
0
1
Order By: Relevance
“…The CPP1 and CPP2 high-performance liquid chromatography (HPLC) analyses of samples were performed using a Shimadzu LC-15C system with a reversed phase HPLC column [Diamond C18 (2), 5 µm, 4.6 mm, Dikma, China]. The elution condition was chosen based on a previously published method with minor changes (18). Briefly, solution A was 0.1% trifluoroacetic acid in deionized water, and solution B was 0.1% trifluoroacetic acid in acetonitrile.…”
Section: High-performance Liquid Chromatography Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The CPP1 and CPP2 high-performance liquid chromatography (HPLC) analyses of samples were performed using a Shimadzu LC-15C system with a reversed phase HPLC column [Diamond C18 (2), 5 µm, 4.6 mm, Dikma, China]. The elution condition was chosen based on a previously published method with minor changes (18). Briefly, solution A was 0.1% trifluoroacetic acid in deionized water, and solution B was 0.1% trifluoroacetic acid in acetonitrile.…”
Section: High-performance Liquid Chromatography Analysismentioning
confidence: 99%
“…The calcium binding capacity was defined as the calcium amount (mg) bound to CPP (g) after chelation. This capacity was measured according to the previously published procedure with minor modifications (13,18). Briefly, samples of CPP were made by dissolving it in 0.02 M of sodium phosphate buffer (pH 7.8) and were subsequently mixed with 5 mM of CaCl 2 .…”
Section: Calcium Binding Capacity In Pbs Buffermentioning
confidence: 99%
“…They also increased zinc uptake similarly to the increase observed in the presence of zinc sulfate alone, suggesting that, for this ion, the peptide did not exert a specific function. A recent study showed that five CPPs named P1-P5, characterized by means of LC-MS/MS, were able to promote Mg 2þ absorption over Ca 2þ in Caco-2 cells growing in a medium enriched with both cations (Cao et al 2017). The fragmentation of aand b-CN generated several antimicrobial peptides.…”
Section: Caseins Deriving Cryptidesmentioning
confidence: 99%
“…The studies showed that protein hydrolysate from several food sources contain calcium-binding peptides. These peptides are bioactive able to promote calcium uptake via epithelium absorption, such as casein phosphopeptides (CPPs) [8,5,9], chicken eggshell matrix proteins [10], and tilapia scale protein hydrolysate [6].…”
Section: Introductionmentioning
confidence: 99%